La mobilité illégale des jeunes diplômés de l’enseignement supérieur - Rim Otmani (Belgeo)
This article aims to describe the new migratory behaviors of young Algerians under 30 years of age, including graduates of higher education. It highlights the issue of professional exclusion, social precariousness and the hardening of immigration policies intrinsically linked to the problematic illegal migration phenomenon. Although illegal mobility is not a recent process in Algeria, it is a new social practice that affects a graduated and conscious population. The illegal mobility of this living force supposed to boost the country’s growth represents the new face of contemporary Algerian migration. It reveals the dysfunctional immigration policies that increasingly prevent the free movement of people and responds to a gap between the needs of young graduates and the solutions proposed to their problems.